Serum HBsAg kinetics and usefulness of interferon‐inducible protein 10 serum in HBeAg‐negative chronic hepatitis B patients treated with tenofovir disoproxil fumarate. Issue 12 (6th July 2015) - Papatheodoridis, G.; Triantos, C.; Hadziyannis, E.; Zisimopoulos, K.; Georgiou, A.; Voulgaris, T.; Vlachogiannakos, I.; Nikolopoulou, V.; Manolakopoulos, S.
Summary The kinetics of serum HBsAg and interferon‐inducible protein 10 (IP10) levels in patients with chronic hepatitis B infection treated with tenofovir are unclear. We evaluated the changes of HBsAg levels and the predictability of IP10 for HBsAg decline in 160 HBeAg‐negative patients receiving tenofovir for ≥12 months. Serum samples taken before and at 6, 12, 24, 36 and 48 months after tenofovir were tested for HBsAg levels. In 104 patients, serum samples before tenofovir were tested for IP10 levels. Compared to before tenofovir, HBsAg levels decreased by a median of 0.08, 0.11, 0.24, 0.33 and 0.38 log10 IU/mL at 6, 12, 24, 36 and 48 months, respectively (P < 0.001). HBsAg kinetics did not differ between nucleos(t)ide analogue(s) naive and experienced patients. The 12‐, 24‐, 36‐ and 48‐month cumulative rates of ≥0.5 log10 HBsAg decline were 8%, 16%, 24% and 41% and of HBsAg ≤100 IU/mL were 9%, 12%, 14% and 18%, respectively. The only factor associated with HBsAg ≤100 IU/mL was lower HBsAg levels before tenofovir (P < 0.001), while HBsAg decline ≥0.5 log10 was associated with higher IP10 levels (P = 0.002) and particularly with IP10 > 350 pg/mL (P < 0.001). In conclusion, tenofovir decreases serum HBsAg levels in both nucleos(t)ide analogue(s) naive and experienced patients with HBeAg‐negative chronic hepatitis B infection. After 4 years of therapy, HBsAg ≤100 IU/mL can be achieved in approximately 20% of patients, particularly in those with low baseline HBsAg levels. HBsAg decline is slow (≥0.5 log10 in 40% of patients after 4 years) and is associated only with higher baseline serum IP10 levels.